Super Fiber Mix (SFM) - forta fi reinforced asphalt pavement - Mohamad Taher, Mohammad Nasir; Bujang, Hazirah (Penerbit UiTM, 2021)
The current design is no longer able to accommodate the increasing traffic load every year, various methods ensure the roads built to last a long time but it eventually causes maintenance costs to exceed affordability and if there is no provision it will be neglected. Conventional pavement materials are not expected to meet the practical demands for present and future highway pavement construction. The maintenance process that is always held will cause the repeated process may come in a considerable expense, ultimately if not designed or constructed properly [1]. All over the world, asphalt mixtures have been used as important materials for the construction of asphalt pavement. Numerous studies have considered factors such as increased axle load, increased traffic movement, critical climatic conditions and even many form failures have prompted researchers to look for several methods to improve the properties of asphalt binders. Although various types of transformers have been used to strengthen asphalt concrete, fibers have attracted the most attention due to their high and desirable properties [2].